Developing a Management Model of PAI Teachers' Competency Improvement Based on Online Networks - Ahsan, Muhammad; Masrukhi, Masrukhi; Haryono, Haryono; Rusdarti, Rusdarti (Universitas Negeri Semarang, 2019)
This study aimed to describe the factual management model of teacher competency improvement focusing on instructional planning, to describe the design of the management model of teacher competency improvement by utilizing online networks, and to know the validity of the management model. This research implemented a Research and Development (R & D) approach. As the focus of this study, the development of the model is in accordance with the theory of a product-oriented model. The products of this study are in accordance with the characteristics and analysis of the needs of Islamic Religious Education (PAI) teachers. The products are regulated through a needs analysis process that meets the needs of the PAI teachers. The products are lesson plans (RPP) to be shared with colleagues. The results of the needs analysis show the importance of online tools in the improvement of the RPP. The management model of teacher competency improvement utilizes online networks using feasibility analysis, guideline preparation, user manuals, and readability tests that show positive responses from experts and users for the development of this model. The development of this model is seen as valid both from the descriptive aspects of the program and the expert analysis. The design of the teacher competency improvement training is deemed feasible to be developed for the benefit of the PAI teachers.